Long-term hypoxia inhibits the passage-dependent stemness decrease and senescence increase of human dental pulp stem cells. (June 2022) - Meng, Hongfang; Wei, Fen; Ge, Zhiqiang; Jin, Jide; Wang, Hua; Wang, Li-sheng; Wu, Chu-tse
Abstract: Dental pulp stem cells (DPSCs) derived from discarded orthodontic teeth are easily obtained and have become a promising source for mesenchymal stem cell-based therapy. However, the pulp tissue is limited, and long-term culture induces cell senescence. Hypoxic culture was expected to be suitable for DPSC expansion, but the results have been contradictory. The aim of this study was to verify the effect of hypoxic culture on human DPSCs (hDPSCs). hDPSCs were isolated and cultured in normoxic (ambient O2 concentration) and hypoxic (5% O2 ) environments from passage 3 (P3) to P6. The biological characteristics of the cells at P4 (short-term culture) and P6 (long-term culture) were evaluated, including the expression of surface markers, cellular proliferation activity, cellular senescence, and spontaneous and induced differentiation. The results showed that the morphology, phenotype, and proliferation activity of hDPSCs were not affected by hypoxic culture. Long-term normoxic culture of hDPSCs induced cell stemness loss and cell senescence, while hypoxic culture could alleviate these effects. The expression of the stemness markers STRO-1 and OCT4 was increased and the number of senescent cells and the expression of the senescence-related genes P53 and TGF-β were reduced by long-term hypoxic culture. Spontaneous osteogenic and adipogenic differentiation did not occur during long-term normoxic culture. However, hypoxic culture suppressed the expression of the osteogenic markers ALP and RUNX-2 and the adipogenic markers PPAR-γ and FABP4. The induced osteogenic and adipogenic differentiation was apparently reduced by hypoxic culture as well. Our findings indicate that long-term hypoxia culture is beneficial to the maintenance of hDPSCs' biological characteristics and provide some insights into their large-scale expansion. Graphical Abstract: ga1 Highlights: Hypoxia didn't influence hDPSCs' proliferation. Hypoxia inhibits the spontaneous stemness decrease and senescence increase of hDPSCs. hDPSCs cultured in normoxia did not undergo spontaneous osteogenic-odontoblast differentiation. Hypoxia suppressed the osteogenic and adipogenic differentiation of hDPSCs. The beneficial effect of hypoxia on the state of hDPSCs was passage dependent.